AN AUDIT OF PRESCRIBING AND ADMINISTRATION OF GASTROPROTECTION IN THE PAEDIATRIC INTENSIVE CARE UNIT. Issue 8 (11th July 2014) - Malesi, G; Isaac, R
Abstract : Aim: Critically ill paediatric patients are considered to be at risk of developing stress ulcers and upper GI bleeds. Gastroprotection is routinely being used in this Paediatric Intensive Care Unit (PICU) to minimise this risk, especially for patients who are nil by mouth (NBM). However, there is a lack of evidence regarding gastroprotection in children and common practice has been mostly developed based on extrapolations from the evidence available for adults. The aim of this audit is to evaluate whether gastroprotection is prescribed and administered appropriately in the Paediatric Intensive Care Unit, according to the Trust's guidelines. Methods: Patient details were collected on a proforma which was piloted, followed by a four week snap shot data collection period. Patients prescribed agents such as rantidine or omeprazole prior to admission to the PICU were not included in the data collection. Age, weight, gastroprotective drug details, gastric pH and enteral intake was collected in order to assess the following standards. 1. Were all patients NBM receiving gastroprotection? 2. Was gastroprotection stopped if the patient was receiving more than 33% enteral feeds. 3. Was a gastric pH between 4 and 6 achieved in patients needing gastroprotection. Results: Fifty four patients were included in the data collection. 84.8% of NBM patients were receiving gastroprotection. Where more than 33% of feeds were given enterally, 26.2% were continued on gastroprotection. A stomach pH between 4–6 was achieved in 70.3% of the patients needing gastroprotection. Within this group a pH recording below 4 was seen in 56% where the dose was not optimised and 11% where one dose was omitted. Only one patient had a pH recording above 6; this patient was receiving a dose too high according to their weight, age and British National Formulary for Children recommendations.1 In 11.1% of patients a gastric pH was not available to assess the adequacy of gastroprotective therapy. Conclusion: The audit results show that an improvement can be made to the Trust guidelines. Re-education on optimising doses and discontinuation of therapy could improve the adherence to the guidelines. Discontinuation of therapy at the appropriate time will cut drug costs and provide nursing time savings. Limitations to this audit include a snap shot approach to the data collection, in particular the gastric pH recording and reasons for omission of doses of gastroprotection.